2010
DOI: 10.1111/j.1365-2982.2010.01569.x
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid agonist WIN55,212 in vitro inhibits interleukin-6 (IL-6) and monocyte chemo-attractant protein-1 (MCP-1) release by rat pancreatic acini and in vivo induces dual effects on the course of acute pancreatitis

Abstract: These findings provide new evidence showing that the pancreatic CB1-r/CB2-r system modulates pro-inflammatory factor levels in rat exocrine pancreatic acinar cells. The dual, time-dependent WIN55,212-induced changes in the development and course of acute pancreatitis support the idea that the role of the endogenous CB receptor system differs according to the local inflammatory status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 63 publications
(74 reference statements)
1
19
0
Order By: Relevance
“…This effect could be completely abolished by previous administration of AM630, which furthermore shows that effects of JWH133 are mediated by CB 2 . In line with our findings, also in Michalski et al (42,43) as well as in Petrella et al (46) studies, decreased effects of the used nonselective cannabinoid agonists were reported after antagonization by AM630. Our finding that some parameters in the AM630-and JWH133-pretreated animals were elevated compared with nonpretreated pancreatitis animals can be explained by additional blockade of eCB at CB 2 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This effect could be completely abolished by previous administration of AM630, which furthermore shows that effects of JWH133 are mediated by CB 2 . In line with our findings, also in Michalski et al (42,43) as well as in Petrella et al (46) studies, decreased effects of the used nonselective cannabinoid agonists were reported after antagonization by AM630. Our finding that some parameters in the AM630-and JWH133-pretreated animals were elevated compared with nonpretreated pancreatitis animals can be explained by additional blockade of eCB at CB 2 .…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, cannabinoid receptors have been shown to play a role in the modulation of secretion of pancreatic enzymes by acinar cells (38), an effect potentially involved in the early phase of acute pancreatitis. Recently, a study showed that another nonselective CB 1 /CB 2 agonist, WIN55,212, had inhibitory effects on synthesis and secretion of proinflammatory cytokines by rat acinar cells in vitro (46). Since this effect was antagonized by AM630, a role of CB 2 was suggested.…”
Section: Discussionmentioning
confidence: 99%
“…13Y17 It was shown that preadministered HU210, a synthetic specific CB1 agonist, protects against cerulein-induced mouse pancreatitis; otherwise, CB1 antagonist rimonabant attenuated the severity of AP in obese mice. 14,15 One of the endogenous cannabinoids, anandamide, when administered before the induction of AP, aggravated pancreatic damage and administered after the induction of AP, reduced the severity of AP, according to the experimental results of Dembinski et al 16 ; whereas Petrella et al 17 got the contrary results in which pretreatment with anandamide before the induction of AP worsened the inflammation, but posttreatment improved the course of the disease.…”
mentioning
confidence: 99%
“…There are two G proteincoupled cannabinoid receptors in the human body, CB1 and CB2 receptors. CB1 receptor is mainly present in the central and peripheral nervous system and CB2 receptor is mainly present in immune cells and the GI tract (23). Both CB1 and CB2 receptors are weakly expressed in the normal pancreas, but this expression increases in the setting of inflammation.…”
Section: Discussionmentioning
confidence: 99%